Growth of red dragon fruit seedlings (Hylocereus costaricensis L.) from two sources of cuttings at various concentrations of shallot solutions. Issue 1 (April 2020) - Dachlan, A; Rafiuddin,; Susanti,; Syam'un, E; Asrul, L; Ulfa, F; Irindu, D
Abstract: One of the obstacles faced in the expansion of the dragon fruit planting area is limited cutting materials to produce high quality seedlings. This study aimed to study the growth of dragon fruit ( Hylocereus costaricensis L.) seedlings from two sources of cuttings at various concentrations of shallots. The research was conducted at the Teaching Farm of the Faculty of Agriculture, Universitas Hasanuddin from November 2018 to February 2019. The trial was set based on Split Plot Design with source of cutting materials as the main plots, consisted of two types of sources ie. apical primary branch and basal primary branch, while concentration of shallots solution as sub plot, consisted of five levels, namely 0, 200, 400, and 600 g.L −1 water, and Rooton-F 10 gL −1 water. The results show that the growth of the dragon fruit seedlings from two different sources of cuttings at various concentrations of shallots did not show significant differences. Sources of cuttings from the basal of the primary branch gave the best results on the number of shoots (2.40 shoots). Application of various concentration of shallot solution resulted in the highest percentage of life cuttings (100%) compared to control (75%). The concentration of shallot solution of 600 g.L −1 water showed the highest results in shoot length (28.33 cm), root length (31.09 cm) and root volume (66.67 mL). The use of Rooton-F as a positive control gave the highest results in root length (31.09 cm) and root volume (66.67 mL).